Analisis Pengukuran Kerja Menggunakan Metode Time Study untuk Meningkatkan Produktivitas di Tina Bakery - Akbar Tawaqqal; Fikrihadi Kurnia (Journal Industrial Engineering and Management (JUST-ME), 2026)
This study aims to analyze the efficiency of bread production processes at the MSME Tina Bakery using the stopwatch time study method. The production process was mapped with an Operation Process Chart (OPC) and a Worker–Machine Chart to identify workflow and the simultaneous involvement of operators and equipment. Work‐time data were collected through direct observation and subsequently analyzed to determine cycle time, normal time, and standard time. The findings indicate that one production cycle requires an observed time of 22,029 seconds, equivalent to approximately 6 hours and 7 minutes. Assuming a performance rating of 100% and a 20% allowance, the standard time is 26,434.8 seconds, or roughly 7 hours and 34 minutes. Proofing is the longest stage, while several manual activities—such as dough shaping—also consume substantial time. The work‐study charts reveal an imbalance between operator and machine times, indicating considerable idle time. Based on these results, this study recommends rescheduling production, productively utilizing waiting periods, and adopting mechanical aids for labor-intensive tasks to improve efficiency and productivity. The study contributes to the development of measurable work standards in the context of food-sector MSMEs